Quantitative economics of corporate crime, punishment and solution - regbonds - Goh, Jing Rong (2019)
Managers engage in gray project investments (i.e. investment projects which have an ambiguous underlying legality). Many research has been conducted to understand the impact of such investments as well as the externalities arising from these investments. However, limited research has been done on providing a better understanding on why managers choose to engage in gray project investments. This thesis serves to shed light on the decision-making process of managers when it comes to gray project investments. Specifically, this thesis focuses on the quantitative economic incentives and provide intriguing insights that are grounded in firm mathematical models. The results help to explain certain real-world behavior by managers on gray project investments. This thesis also provides a novel solution – the Regbonds – that can potentially mitigate the level of gray project investments in the macro-economy. In the micro-setting, Regbonds are able to mitigate agency problems which helps to align the interests between shareholders and managers. Finally, I do hope that the thesis can help us better understand the underlying nature of gray project investments and the Regbonds can help to mitigate the real-world problems associated with these investments. This thesis consists of three chapters, the abstract for each chapter is as follows.